Ethanolic Extract of Tamarindus indica Leaves Lowers Total Cholesterol, Triglycerides, and HDL but Without Affecting LDL in Hyperlipidemic Rats - Susiloningsih, Tri; Christijanti, Wulan; Marianti, Aditya; WH, Nugrahaningsih (Universitas Muhammadiyah Surakarta, 2025)
Hyperlipidaemia is a condition of increased lipid levels, especially cholesterol, triglycerides, LDL and an abnormal decrease in HDL in the blood. Tamarind leaves contain flavonoid and quercetin compounds that have the ability as antihyperlipidemia agents. The purpose of this study was to examine the effect of tamarind leaf ethanol extract on the lipid profile of hyperlipidaemia rats. Samples of 16 male Wistar rats were divided into 4 groups; Control group and the tamarind leaf ethanol extract treatment group was divided into 3, namely P1 350 mg/kgBB, P2 500 mg/kgBB, and P3 650 mg/kgBB. All rats were given lard 3 mL/head/day for 2 weeks. In weeks 3 and 4, rats were given extract of Tamarindus indica leaves and 2 hours interval was given lard. The data obtained were statistically analysed using one-way ANOVA and the Least Significant Difference (LSD) test at the 95% confidence level. In this study, HDL levels decreased along with reductions in total cholesterol and triglycerides, but had no effect in reducing LDL levels. Reduced cholesterol synthesis limits substrate availability for HDL formation, resulting in proportional decreases in HDL-C. The conclusion of this study is that tamarind leaf ethanol extract has an effect in reducing lipid profile levels.